The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1098/rsbl.2016.0407
|View full text |Cite
|
Sign up to set email alerts
|

Strong phylogenetic inertia on genome size and transposable element content among 26 species of flies

Abstract: While the evolutionary mechanisms driving eukaryote genome size evolution are still debated, repeated element content appears to be crucial. Here, we reconstructed the phylogeny and identified repeats in the genome of 26 Drosophila exhibiting a twofold variation in genome size. The content in transposable elements (TEs) is highly correlated to genome size evolution among these closely related species. We detected a strong phylogenetic signal on the evolution of both genome size and TE content, and a genome con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
68
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(89 citation statements)
references
References 29 publications
19
68
2
Order By: Relevance
“…Rather, genome size evolution is reliant upon phylogenetic patterns. These results are supported by recent work on genome size evolution in Drosophila species [39]. Here, Sessegolo et al .…”
Section: Discussionsupporting
confidence: 83%
“…Rather, genome size evolution is reliant upon phylogenetic patterns. These results are supported by recent work on genome size evolution in Drosophila species [39]. Here, Sessegolo et al .…”
Section: Discussionsupporting
confidence: 83%
“…Interestingly, we did not observe a significant correlation between the genome size (Fig. 6) and the proportion of LTR-retrotransposons (Spearman correlation test r  = 0.41, p -value = 0.07115) whereas it has been shown that the proportion of repeats is correlated with Drosophila genome size, in link with phylogenetic inertia [39]. It is possible that the lack of correlation comes from the fact that we are considering only LTR-retrotransposons.…”
Section: Resultsmentioning
confidence: 72%
“…While species with higher 47 O'Grady 2006; Clark et al 2007). The sequenced species, show striking differences between TE 63families and orders, and make up differing proportions of the genome, between 5 and 40% across 64 the tree (Sessegolo et al 2016). Additionally, the TE content of two species in the D. affinis 65…”
mentioning
confidence: 99%